A Study the review of computer education in relation to the Academic Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Computer is one of the most useful and powerful tool for everyone. Computers play a crucialrole in the classroom as a means of increasing efficiency. As the changes of world is becoming very fast,computers have occupied a powerful place in both societal and educational purpose. Every dimension ofmodern life involves computer in some way or another. People who do not have any experience aboutcomputers face great difficulty in their daily work. Students of all ages require the help of computers tostay up to date. Luckily, most students over the past few decades have had many chances to learn aboutcomputers in school. Thus computer education has come to be accepted as an essential element ofmodern scientific era. Students' perspectives on the value of computer education in improving theiracademic achievement in school were investigated.